The martial ethic in early modern Germany civic duty and the right of arms - Tlusty, B. Ann (Early modern history: society and culture, 2011)
For German townsmen, life during the sixteenth and seventeenth centuries was characterized by a culture of arms, with urban citizenry representing the armed power of the state. This book investigates how men were socialized to the martial ethic from all sides, and how masculine identity was confirmed with blades and guns.